2006
DOI: 10.1016/j.powtec.2006.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of floc size, strength and structure under various coagulation mechanisms

Abstract: Flocs generated by various coagulation mechanisms exhibit different size, strength and structure. The properties and fractal dimensions of flocs formed under three common coagulation mechanisms, i.e. charge neutralization, sweep and bridging, were investigated at various hydraulic conditions. The results showed that the floc size decreased with the increasing average velocity gradient G and the stable floc size exponent γ was of the following hierarchy: charge neutralization (0.6107) N sweep (0.5618) N bridgin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
92
0
15

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 310 publications
(119 citation statements)
references
References 34 publications
(39 reference statements)
7
92
0
15
Order By: Relevance
“…The clusters formed under these conditions are open, with a fractal dimension of about 1.6-1.7, slightly lower than those found in DLCA [60]. However, in practically relevant conditions, this aggregation process is carried out in the presence of shear, which as expected increases the density of clusters, and therefore their fractal dimensions, to values ranging from 2.4 to 2.8, depending on the shear rate used [61]. It is generally observed that clusters obtained from bridging flocculation have lower fractal dimension than the one formed from their counterparts obtained by just addition of high concentration of electrolytes under otherwise identical conditions [62].…”
Section: Bridging Flocculationmentioning
confidence: 59%
“…The clusters formed under these conditions are open, with a fractal dimension of about 1.6-1.7, slightly lower than those found in DLCA [60]. However, in practically relevant conditions, this aggregation process is carried out in the presence of shear, which as expected increases the density of clusters, and therefore their fractal dimensions, to values ranging from 2.4 to 2.8, depending on the shear rate used [61]. It is generally observed that clusters obtained from bridging flocculation have lower fractal dimension than the one formed from their counterparts obtained by just addition of high concentration of electrolytes under otherwise identical conditions [62].…”
Section: Bridging Flocculationmentioning
confidence: 59%
“…Many researchers [6][7][8][9][10][11][12] have found that, in addition to slow-mixing conditions, coagulants and coagulation mechanisms have significant effects on the size, strength and structure of flocs. This indicates that the effects of slow-mixing on coagulation are probably influenced by coagulants and coagulation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The use of polymers in water treatment can achieve rapid flocculation and result in better settling or filtrating behaviors. Several studies have demonstrated that various flocculation mechanisms are responsible for different floc characteristics (Li et al, 2006). It has been established that the polymers can flocculate particles via bridging, charge neutralization, electrostatic patch and depletion flocculation mechanisms.…”
Section: Introductionmentioning
confidence: 99%